Calciothermic Synthesis of Very Fine, Hydrogenated Ti and Ti–Nb Powder for Biomedical Applications. Issue 3 (9th December 2019) - Lindemann, Inge; Gebel, Bernhard; Pilz, Stefan; Uhlemann, Margitta; Gebert, Annett
Abstract : Due to their excellent biocompatibility, titanium and titanium–niobium alloys are especially interesting for biomedical applications. With regard to favorable near‐net shape production, Ti powder synthesis is the key hurdle. Extensive research has been in progress for alternative synthesis methods since decades. Herein, an efficient alternative method to the conventional powder production process to prepare spherical powders with very small sizes (<45 μm) for high‐strength materials is shown. Very fine, hydrogenated Ti and Ti–Nb alloy powders are stable in air and are synthesized by calciothermic reduction in hydrogen. The herein presented reduction using CaH2 starts directly from the oxides instead of chlorides. Correlations of size and morphology of the as‐synthesized TiH2 and (Ti, Nb)H2 powders with the precursors (TiO2, Nb2 O5, and CaH2 ) are illustrated and are used to tailor the desired powders. Abstract : An alternative method for the synthesis of fine, hydrogenated titanium powder production is reported. Hydrogenated Ti and Ti–Nb powders are stable in air and are prepared by calciothermic reduction with sizes well below 45 μm. Properties of the final powders are tailored by the choice of the precursors, such as TiO2, Nb2 O5, and CaH2 .